Imaginal retraining reduces craving for high-calorie food. (1st March 2023) - Moritz, Steffen; Göritz, Anja S.; Kühn, Simone; Gallinat, Jürgen; Gehlenborg, Josefine
Abstract: Imaginal retraining (IR) is a treatment derived from approach bias modification to reduce strong craving for high-calorie food. The push component (IRpush ) seems to be the most effective element according to a recent dismantling trial. Conclusions derived from prior studies are limited, however, by small sample sizes and restriction of participants to women. The present study aimed to overcome these limitations and also tested a new variant of IR (3P; decoupling with the elements pull, pause, push ), which has previously been found to be more effective than the standard protocol in individuals with problematic alcohol use. The study was conducted online. A total of 1, 106 participants with strong craving for high-calorie food were randomized to different brief interventions of IR or a passive control group. Before and after the interventions, participants indicated their craving for high-calorie food and appraised food pictures. The main conditions of interest were IRpush and 3P. The other two experimental conditions did not contain a motor element and served as active control conditions. IRpush proved the most effective intervention and reduced craving by approximately 18%, which was significantly larger than in the passive control group. IRpush worked especially well for those with higher initial weight, higher cravings, and more dysfunctional eating behavior. The novel 3P technique significantly reduced craving across time and was especially effective for those with high BMI and craving. The study suggests that a simple self-help component of imaginal retraining, IRpush, can decrease craving for high-calorie food to a relevant extent. Future trials should elucidate whether different forms of substance-related and behavioral addictions require adapted IR or 3P protocols to increase effectiveness.